Everyday identities in Malaysian Chinese’s subjectivities - Lee , Yok Fee (Universiti Kebangsaan Malaysia, 2009)
In the studies of Malaysian Chinese identity, most writings are based on macrolevel analysis, which mainly focus on social structures but not the social actors. The characteristics of the social actors are always assumed as fixed, passive and homogeneous. The abilities, creativity and roles of social actors are often overlooked. Ironically, there are very few micro-level studies conducted to understand the formation of Chinese identity in Malaysia. This article is a modest attempt by the author to answer these main questions: What is the knowledge of Chinese Malaysians about their everyday identity as Chinese in Malaysia and how do they create their identity in everyday life? In a research conducted by the author the abductive approach was employed, which refers to the process that privileges the social actors’ account to generate social scientific knowledge. For that, in-depth interview method was applied to gather data from twelve informants over a period of eighteen months. The result shows that, as social actors, Malaysian Chinese exhibit their abilities, creativity and reasoning in the process of forming their identity. They have their own, though often disorganised, logical ways and methods of conceptualising their identity. The everyday identity formed by the Malaysian Chinese is fluid, dynamic and situational. The formation of the everyday identity is determined by the stock of knowledge, contexts and also their interactions with others. The typology of everyday identity formation can be divided into ‘stimulated subjectivity’, ‘structural subjectivity’ and ‘binary oppositional subjectivity’.